Electrospinning of synthesized chitosan nanoparticles embedded with polyurethane for vascular graft - Ranjeeta Subramaniam, 1994- , author 611975; Saravana Kumar Jaganathan, supervisor 599042; Fakulti Biosains dan Kejuruteraan Perubatan 538915 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Bio-Perubatan)) - Universiti Teknologi Malaysia, 2017